2005
DOI: 10.1016/j.ejvs.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins in Vascular Disease—A Review

Abstract: Introduction. There is growing evidence that heat shock proteins (HSPs), a family of stress-inducible proteins may be involved in the pathogenesis of atherosclerotic vascular diseases. Here, we systematically review the evidence behind this notion. Methods. A detailed literature search and extensive bibliographic review of literature relating to HSPs and atherosclerotic vascular disease. Results. Atherosclerotic vascular disease is classified into four main areas of presentation: carotid, coronary, aortic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 62 publications
1
59
0
1
Order By: Relevance
“…18 Current evidence suggests that antibody titres to Hsps are elevated in patients with vascular disease, and that this is related to the severity of atherosclerosis. 19 In the current study, we have shown anti-Hsps are raised in obesity, in the absence of clinically evident coronary disease, but that they are not significantly raised in overweight subjects.…”
Section: Discussionmentioning
confidence: 43%
“…18 Current evidence suggests that antibody titres to Hsps are elevated in patients with vascular disease, and that this is related to the severity of atherosclerosis. 19 In the current study, we have shown anti-Hsps are raised in obesity, in the absence of clinically evident coronary disease, but that they are not significantly raised in overweight subjects.…”
Section: Discussionmentioning
confidence: 43%
“…Several studies have investigated the link between cardiovascular disease (CVD) and serum/plasma levels of HSP or HSP auto-antibodies. A clear link between HSP60 serum levels and CVD has been shown [17]. However, the connection between HSP70 or anti-HSP70 antibody levels and CVD or CVD risk phenotypes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Their primary function is to fulfill chaperoning activity: as new proteins are being produced by ribosomes, HSPs assist in correct folding of polypeptide chains into functional protein, and after a stress event, HSPs assist in refolding or degradation of damaged or denatured proteins (2 ).…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%